The effect of remdesivir on heart in pregnant female rats - Ibrahim, Muhammed K. (Edelweiss Applied Science and Technology, 2024)
Remdesivir is the first medication that the FDA has authorized for use in treating COVID-19 pandemic. To evaluate the effect of remdesivir on level of sodium and potassium in blood and its effect on heart tissue in pregnant female rats. 10 pregnant female rats were used and split into two groups. 1ST group was a control group that was treated with distilled water every 48 hours, starting from 5th day of pregnancy until 19th day. 2nd group was treated with remdesivir at a concentration of 5 mg/kg body weight, every 48 hours, beginning on the 5th day of pregnancy and ending on the 19th day. On day 20, the animals were sacrificed and blood samples were taken to conduct the required tests, then an autopsy was performed to remove heart and make histological sections. Giving remdesivir was administered to the 2nd group, the blood serum potassium level significantly decreased and the sodium level significantly increased , additionally, blood congestion and hemorrhage occurred, some blood cells lysed, and there were severe cases of inflammatory cell infiltration in the heart sections compared to the 1st group. The use of remdesivir caused an imbalance in the level of electrolytes in blood and tissue damage to the heart muscle.